Effect of Prevention Measures on Incidence of Human Listeriosis, France, 1987-1997 - Véronique Goulet (Emerging Infectious Diseases, 2001)
To assess the impact of preventive measures by the food industry, we analyzed food monitoring data as well as trends in the incidence of listeriosis estimated through three independent sources: the National Reference Center of Listeriosis; a laboratory-based active surveillance network; and two consecutive nationwide surveys of public hospital laboratories. From 1987 to 1997, the incidence of listeriosis decreased by an estimated 68%. A substantial reduction in the proportion of Listeria monocytogenes-contaminated products was observed at the retail level. The temporal relationship between prevention measures by the food industry, reduction in L. monocytogenes-contaminated foodstuffs, and reduction in listeriosis incidence suggests a causal relationship and indicates that a substantial part of the reduction in illness is related to prevention efforts.